STRATEGI PEMBERDAYAAN MASYARAKAT DALAM MENGEMBANGKAN EKONOMI KREATIF DI ERA SOCIETY 5.0 - Asrini Habeahan; Chacha Iqna Veby Tarigan; Desryana Sinaga; Devi Aulia; Eva Arnel Silalahi; Ledydiani Margareth Purba; Rika Inriani Sinaga; Prini Desima Evawani Ambarita (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The rapid advancement of digital technology in the era of Society 5.0 has created significant opportunities for communities to actively participate in economic development driven by creativity and innovation. However, this digital transformation also presents critical challenges, such as digital literacy gaps, limited access to technology, and a lack of entrepreneurial capacity, particularly at the local level. This study aims to identify effective community empowerment strategies to support the growth of the creative economy in the Society 5.0 era. The research adopts a literature review approach by analyzing relevant sources on community empowerment, creative economy, and Society 5.0. The findings indicate that a comprehensive empowerment strategy should include digital literacy enhancement, local creative community strengthening, entrepreneurship education, and collaboration among government, private sector, and community stakeholders. These approaches are reinforced by participatory empowerment models and the utilization of digital technology as an accelerator of social and economic transformation. The study recommends integrating policies that support continuous training, creative business incubation, and the adoption of technology tailored to local needs to foster inclusive, competitive, and adaptive creative communities. Thus, community empowerment is not only a solution to bridge the digital divide but also a foundational element for sustainable creative economy development amid the complexities of the Society 5.0 landscape.